Summary Proceedings: of the Fifty-Third Annual Meeting of the Board of Governors October 6-8, 1998 - International Monetary Fund; The World Bank (Washington, D.C., 1998)
These contains the summary proceedings include statements, or portions of statements, relating to the work of the Fifty-Third Annual Meeting of the Board of Governors of the International Monetary Fund, held in Washington, D.C., from October 6-8, 1998.
usc 27/08/2021
Ref.